The Promise of Blue Carbon Climate Solutions: Where the Science Supports Ocean-Climate Policy - Christianson, Anne B.; Cabré, Anna; Bernal, Blanca; Baez, Stacy K.; Leung, Shirley; Pérez-Porro, Alicia; Poloczanska, Elvira (Frontiers in Marine Science, 2022)
The ocean is gaining prominence in climate change policy circles as a tool for addressing the climate crisis. Blue carbon, the carbon captured and stored by marine and coastal ecosystems and species, offers potential as a “nature-based solution” to climate change. The protection and restoration of specific ocean ecosystems can form part of a climate response within climate mitigation policies such as Nationally Determined Contributions under the United Nations Framework Convention on Climate Change. For mitigation policies that seek to implement management actions that drawdown carbon, ecosystem sequestration and emissions must be measurable across temporal and spatial scales, and management must be practical leading to improved sequestration and avoided emissions. However, some blue carbon interventions may not be suitable as a climate mitigation response and better suited for other policy instruments such as those targeted toward biodiversity conservation. This paper gives context to numerous blue carbon sequestration pathways, quantifying their potential to sequester carbon from the atmosphere, and comparing these sequestration pathways to point-source emissions reductions. The applicability of blue carbon is then discussed in terms of multiple international policy frameworks, to help individuals and institutions utilize the appropriate framework to reach ocean conservation and climate mitigation goals.